School Leaders Unity Practices Level and Students Unity Level in Secondary School - Alias, Bity Salwana; Ishak, Mohd Radzi (International Journal of Psychosocial Rehabilitation, 2020)
Malaysia education system has been designed to promote unity. In parallel to that, multi- racial citizens have to speak national language, follow the same curriculums and sit for the same examinations. Vision Schools and Student Integration Plan for Unity was also implemented. In addition, school leaders were reminded to promote unity. However, unity index kept on decreasing. Therefore, the purpose of this study is to determine unity practices level among secondary school leaders, to determine unity level among secondary school students and to determine the relationship of the two variables. For the methodologies, sample size are 542 students who answered questionnaires as research instrument. Research team has visited the sample school to collect data which was descriptively analyzed to obtain mean score and standard deviation and inferentially analyzed to determine r values. Results showed that school leaders’ unity practice level and students’ unity level were high (mean score of 3.60 and 3.97 respectively), and there was a significant relationship but at the moderate level between unity practices and unity level. r value equal to 0.480. To conclude, what has been done is still not enough to increase unity to the highest level. The implication is, what has been stated in unity model is absolutely true, therefore, courses or trainings that can increase the ability of school leaders to instill unity values among the students must be implemented. These results also implied that school leaders’ effort to increase unity level is still not enough, therefore actions to tackle the issue is needed.